Immune cell-ovarian tumor cell adhesion through MUC16 and immunocytokine - Horibata, Sachi (My University, 2010)
Natural killer (NK) cells are immune cell types that function normally to eliminate tumor cells by forming an immune synapse. However, we have shown that the presence of mucin, MUC16, on the surface of epithelial ovarian tumor cells inhibits the function of NK cells in two ways: 1) steric barrier 2) inducing inhibitory signaling through Siglec-9. To increase recognition of tumors by NK cells, we utilized the immunycytokine, KSIL-2, which activates NK cells through IL-2 and mediates ADCC via the KS antibody. Using a plate adhesion assay, we demonstrate that KSIL-2 mediates increased NK-tumor cell interactions. Our data shows that KSIL-2 can overcome the immune evasion mediated by the large MUC16 molecule.
19 p.
Keywords: Obstetrics and Gynecology; Biochemistry